Wiktor Pielewin wobec kultury masowej. Powieść Empire V - Siepietowska, Joanna (Acta Polono-Ruthenica, 2011)
In my article I write about Victor Pielevins relation with mass culture. On the one hand, Pielevin is a supporter of mass culture by taking advantage of it to promowe his novels. On the other hand, the Russian writter is open to criticism too. In Empire V he shows the most current problem, considering money which is a driving force of many people. In his opinion people are in a tragic siutuation to live in the culture of consumption.